Development and evaluation of a quick method for optimizing a space and signal timing plan for isolated signalized intersections - Ratrout, Nedal; Assi, Khaled (Transport, 2021)
One major cause of congestion at intersections is the fluctuation of traffic demand during the day. This phenomenon necessitates developing new models that can be used to enhance the performance of signalized intersections. We suggest a quick procedure for optimizing signal timing plans after identifying the best phasing scheme and selecting optimal lane allocation (space optimization) for any volume characteristics during the day at a typical four-leg intersection. The main contribution of this study is developing a method for collectively optimizing a signal-timing plan, intersection space, and phasing scheme. TRANSYT-7F, SYNCHRO and HCS2010 were used to assess the developed models in a case study. It was found that regardless of the optimization software used for timing-plan optimization, optimizing both space and timing plan together produce significant reductions in average intersection delay compared to optimizing only the timing plan. Furthermore, this study showed that the developed model, which optimizes space and time, consistently provided better results in terms of average intersection delay compared to TRANSYT-7F, SYNCHRO and HCS2010 in the case study. First published online 18 May 2020